Efficacy and safety of Shenfu injection for the treatment of post-acute myocardial infarction heart failure: A systematic review and meta-analysis - Yanhua Wu; Yanhua Wu; Yanhua Wu; Shuang Li; Zunjiang Li; Zhaofan Mo; Ziqing Luo; Dongli Li; Dongli Li; Dongli Li; Dawei Wang; Wei Zhu; et al. (Frontiers Media S.A., 2022)
Objective: This systematic review and meta-analysis aimed to investigate the adjuvant effect and safety of Shenfu injection (SFI) on the treatment of post-acute myocardial infarction heart failure (PAMIHF).Methods: Seven databases were searched to identify randomized controlled trials (RCTs) associated with SFI and PAMIHF treatment from May 1990 to May 2022. Primary outcomes included NT-proBNP and left ventricular ejection fraction (LVEF), and secondary outcomes included total effective rate, BNP, heart rate (HR), cardiac output (CO), and adverse event (AE). The risk of bias evaluation was assessed by the ROB2 tool, meta-analysis, subgroup analysis, sensitivity analysis, and publication bias were conducted by RevMan5.3 software, and the Grade of Recommendations, Assessment, Development, and Evaluations (GRADE) system was used to evaluate the quality of evidence of meta results.Results: A total of 36 studies with 3231 PAMIHF patients were included. The meta results suggested that adjuvant SFI therapy was superior to conventional medical therapy alone. It improved the total effective rate [RR = 1.33; 95% CI (1.25.1.40); p < 0.00001], increased LVEF [SMD = 0.98; 95% CI (0.71, 1.24); p < 0.00001], and decreased HR [SMD = −1.14; 95% CI (−1.28, −0.99); p < 0.00001]. In addition, adjuvant SFI therapy (9.73%, 66/678) had a rate of AE lower than that of conventional medical therapy alone (21.7%, 147/677) when regarding safety [RR = 0.45; 95% CI (0.35, 0.57); p < 0.00001]. The quality of the evidence for the outcomes was rated from "very low" to "moderate."Conclusion: Adjuvant SFI therapy was safer to improve the total effective rate and the heart function of PAMIHF patients. However, well-designed RCTs were needed to confirm the efficacy and safety of adjuvant SFI therapy in PAMIHF treatment due to the low quality of the evidence for the outcomes caused by a small sample size and unclear risk of bias existed in included studies.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=151856), identifier CRD42020151856.